Emerging trends in sacubitril/valsartan research: A bibliometric analysis of the years 1995–2021. Issue 31 (5th August 2022) - Lai, Ping; Xue, Jin-Hua; Xie, Mu-Jin; Ye, Jin-Hua; Tian, Ke-Jun; Ling, Jia-Yuan; Zhong, Wen-Ting; Chen, Dong; Zhong, Yi-Ming; Liao, Yong-Ling
Abstract : Background: Sacubitril/valsartan has been approved for the treatment of heart failure (HF) patients with reduced ejection fraction; since then, it gradually became a new star drug in the therapy of HF. Nevertheless, the effectiveness of sacubitril/valsartan remains under investigation. Thus far, only a few bibliometric studies have systematically analyzed the application of sacubitril/valsartan. Methods: Publications on sacubitril/valsartan were retrieved from the Web of Science Core Collection on April 29, 2021. Data were analyzed using Microsoft Excel 2019 (Redmond, WA), VOS viewer (Redmond, WA), and Cite Space V (Drexel University, Philadelphia, PA). Results: A total of 1309 publications on sacubitril/valsartan published from 1995 to 2021 were retrieved. The number of publications regarding sacubitril/valsartan increased sharply in the last 6 years (2015–2021), and American scholars authored >40% of those publications. Most were published in the European Journal of Heart Failure, the United States was the bellwether with a solid academic reputation in this area. Solomon published the highest number of related articles and was the most frequently cited author. "Heart failure" was the leading research hotspot. The keywords, "inflammation, " "fibrosis, " and "oxidative stress" appeared most recently as research fronts. Conclusions: Research attention should be focused on clinical trial outcomes. Considering its effectiveness in HF, the mechanisms and further applications of sacubitril/valsartan may become research hotspots in the future and should be closely examined.